PENGGUNAAN EKSTRAK KULIT BUAH NAGA MERAH (Hylocereuscostaricensis (F.A.C. Weber) Britton & Rose.) DALAM FORMULASI PEWARNA RAMBUT - Masyithah, Cut; Maimunah, Siti; Zuhairiah, Zuhairiah; Sitorus, Cahaya Amalia (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Hair is a symbol of beauty in humans which is one of the adnexa (parts) of the skin that grows from the skin. Hair grows from the root, hair that is in the dermis layer, and through the hair follicle channel out of the skin. There are some differences in each hair such as type, shape, amount, and color. Dragon fruit peel is an agricultural waste that contains high anthocyanin natural dyes. Anthocyanin is a dye that plays a role in giving red color which has the potential to be a natural colorant for food and can be used as an alternative to synthetic dyes that are safer for health. Anthocyanin was taken by the extraction method. The results showed that the higher the concentration of the adjuvant used, the darker the gray hair. The use of auxiliary materials in a concentration of 0.5% produces a brownish-black color, and a concentration of 1% produces a dark black color. The preparation of gray hair dye made with the formula of 2.5% dragon fruit peel extract and 1% adjuvant produces a deep black color, so pyrogallol, copper (II) sulfate, xanthan gum with a concentration of 0.5% are used in order to distinguish changes on white hair (grey), due to the EKBN formula or from added additives.